Thermal Inactivation of a Cold-Active Esterase PMGL3 Isolated from the Permafrost Metagenomic Library - M.V. Kryukova; L.E. Petrovskaya; E.A. Kryukova; G.Yu. Lomakina; S.A. Yakimov; E.G. Maksimov; K.M. Boyko; V.O. Popov; D.A. Dolgikh; M.P. Kirpichnikov (Biomolecules, 2019)
PMGL3 is a cold-adapted esterase which was recently isolated from the permafrost metagenomic library. It exhibits maximum activity at 30 °C and low stability at elevated temperatures (40 °C and higher). Sequence alignment has revealed that PMGL3 is a member of the hormone-sensitive lipase (HSL) family. In this work, we demonstrated that incubation at 40 °C led to the inactivation of the enzyme (t1/2 = 36 min), which was accompanied by the formation of tetramers and higher molecular weight aggregates. In order to increase the thermal stability of PMGL3, its two cysteines Cys49 and Cys207 were substituted by the hydrophobic residues, which are found at the corresponding positions of thermostable esterases from the HSL family. One of the obtained mutants, C207F, possessed improved stability at 40 °C (t1/2 = 169 min) and increased surface hydrophobicity, whereas C49V was less stable in comparison with the wild type PMGL3. Both mutants exhibited reduced values of Vmax and kcat, while C207F demonstrated increased affinity to the substrate, and improved catalytic efficiency.